Webinar: Pencegahan Stunting Pada Remaja Di MAN 2 Surakarta - Puspitasari, Dyah Intan; Hanifah, Dina Nur; Persada, Tashila Zahra (Abdi Geomedisains, 2024)
Adolescents who have poor nutritional status, rarely eat breakfast, consume less fruit and vegetables, and have low knowledge of stunting can be risk factors for giving birth to stunted babies in the future. One strategy that can be done to increase student knowledge is through the provision of education in the form of webinars. The webinar activity with the theme "Adolescent Stunting Prevention at MAN 2 Surakarta" was conducted by providing information to students about the role of adolescents in stunting prevention, healthy lifestyles in adolescents, and processing healthy menus for adolescents. This activity went well and was attended by 65 students. Through this Webinar activity, adolescent knowledge related to stunting increased significantly (p = 0.000) which was indicated by an increase in the post-test score (9.85) compared to the pretest score (7.98). Increased knowledge of adolescents related to stunting can be one of the strategies to prevent stunting in the future. Similar program with other health issues can be given to adolescents in order to increase their understanding to implement a healthy lifestyle.